Effectiveness of Hindmilk Feeding on Weight Gain Among Low-Birth-Weight Infants - Abiyoga, Aries; Meihartati, Tuti; Kristiani, Denny; Bandung, Murti (Journal of Applied Nursing and Health, 2026)
Background: Low Birth Weight (LBW) infants are at high risk of morbidity and growth problems. Hindmilk, which is rich in fat and calories, is proposed to improve weight gain, but evidence remains limited. This study examined the effect of hindmilk feeding on weight gain in LBW infants. Methods: This pre-experiment design and was reported in accordance with the TREND guideline. A total of 15 LBW infants admitted to the Perinatology Unit of Malinau Hospital were recruited using purposive sampling. The independent variable was hindmilk feeding, while the dependent variable was infant weight gain. Data were collected using the Standardised Human Observation Sheet (SHOS) and analysed using the paired sample t-test. Results: The findings showed a significant increase in infant body weight after the hindmilk intervention compared with baseline measurements. The mean body weight after intervention was higher than before intervention, with a statistically significant difference (p = 0.001). These results indicate that hindmilk feeding contributed positively to weight gain among LBW infants. Conclusion: Hindmilk feeding significantly improved weight gain among LBW infants at Malinau Hospital. Therefore, hindmilk feeding may be recommended as an effective nutritional intervention for the management of LBW infants, particularly in resource-limited and remote healthcare settings.